A method for accurately measuring the chloride ion content in the rust layer on the surface of bronze artifacts
By using hydrogel to adsorb and test the rust layer on the surface of bronze artifacts, combined with AC impedance and circuit fitting, the problems of insufficient measurement accuracy and damage to the surface of the artifact in the existing technology were solved, and the effect of non-destructive accurate measurement and rust removal was achieved.
Patent Information
- Application Number
- CN202310274161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-09
- Filing Date
- 2023-03-21
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2043-03-21
AI Technical Summary
The existing technology for measuring the chloride ion content in the rust layer on the surface of bronze artifacts has the problems of insufficient accuracy, severe damage to the surface of the artifacts, and complex and expensive equipment.
Hydrogel was used as the electrochemical test medium. ALg-CS-Ag hydrogel was prepared, and the rust powder on the surface of bronze was adsorbed. AC impedance test was performed, and the chloride ion concentration was obtained by combining equivalent circuit fitting.
It has achieved non-destructive and accurate determination of the chloride ion content in the rust layer on the surface of bronze ware, and can complete the rust removal work during the measurement process with an error within 10%.
Smart Images

Figure CN116256396B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bronze protection, and in particular relates to a method for accurately measuring the chloride ion content in the rust layer on the surface of bronze. Background Art
[0002] Copper-based artifacts are plagued by what's known as "bronze disease," defined as the interaction of various chlorides in copper rust with moist air, often accompanied by corrosion of the copper alloy itself. This disease not only corrodes the bronze's surface but also exacerbates the corrosion process. The chemical reaction product is a light-green, powdery basic copper chloride. Therefore, the detection and removal of active chloride ions on the surface of bronze artifacts is a paramount concern in bronze preservation.
[0003] For ion detection, various methods have been developed, including: fluorescence sensors, surface plasmon resonance sensors, inductively coupled plasma mass spectrometry (ICPMS) and atomic absorption / emission spectroscopy (AAS / AES), surface enhanced Raman scattering (SERS) spectroscopy and nanoparticle-based colorimetric determination, etc. Although these methods have obvious advantages in some cases, such as high sensitivity and strong anti-interference, there are still some limitations, including cumbersome sample pretreatment, the need for complex and expensive equipment, the inability to quantitatively and accurately determine the ion content, and irreversible damage to the surface of bronze. Electrochemical methods have attracted widespread attention due to their simplicity, convenience, low cost, high sensitivity, and suitability for real-time monitoring and on-site analysis. For example, electrochemical sensors for Cu 2+ Nanomolar and / or subnanomolar concentrations can be easily reached in water samples, but electrochemical methods can also have irreversible effects on the bronze surface and may even exacerbate corrosion. Therefore, a material is needed as a medium for electrochemical testing to indirectly measure ion concentrations.
[0004] Hydrogels are relatively gentle materials with numerous advantages, including highly porous 3D continuous networks, good water permeability, ease of modification, biocompatibility, and good degradability. They have broad applications in tissue engineering, wound dressings, antifouling coatings, and other fields, and have also made progress in copper rust removal. Therefore, the present invention attempts to use hydrogels for rust removal followed by electrochemical measurement, effectively avoiding direct damage to the bronze surface and maximally reducing the chloride ion content on the bronze surface. Summary of the Invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for accurately determining the chloride ion content of the rust layer on the surface of bronze ware. The method has the advantages of being non-destructive, highly accurate, convenient and fast.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for accurately measuring the chloride ion content of the rust layer on the surface of bronze artifacts comprises the following steps:
[0008] 1) Hydrogel Synthesis: Water-soluble chitosan (CS) and sodium alginate were dissolved in deionized water. A polyvinyl alcohol (PVA) solution was then added at 25-35°C and stirred to obtain a homogeneous sodium alginate-PVA-chitosan solution. A silver nitrate (AgNO3) solution was then added and stirred for 5-30 minutes. The mixture was transferred to a Petri dish and dried to obtain the ALg-CS-Ag hydrogel.
[0009] 2) Preparation of artificial rust powder: Mix 2.00g of basic copper chloride with 0.00g, 0.002g, 0.01g, and 0.02g of copper chloride, respectively. Add the mixture to a beaker and shake until the mixed powder is smooth. Number the mixtures A1, A2, A3, and A4, respectively.
[0010] 3) Adsorption process: Cut the ALg-CS-Ag hydrogel obtained in step 1) into small pieces and add them to A1, A2, A3, and A4, respectively, ensuring that one side of the hydrogel is in full contact with the rust powder for adsorption. Simultaneously, attach a PAAm-CS-Ag hydrogel of the same size to the surface rust layer of a bronze fragment for adsorption, numbered A5. Wait 21-27 hours, then remove or peel off the adsorbed hydrogel.
[0011] 4) Soaking the adsorbed hydrogel obtained in step 3) in deionized water until it is completely swollen (generally takes about 8-14 hours), and numbering them as B1, B2, B3, B4, and B5 respectively;
[0012] 5) Performing an AC impedance test on the fully swollen hydrogel obtained in step 4), and performing an equivalent circuit fitting on the test results to obtain a resistance value; plotting the relationship between the reciprocal resistance values of hydrogels B1, B2, B3, and B4 and the chloride ion concentration and performing a linear fit to obtain a fitting function; substituting the reciprocal resistance value corresponding to hydrogel B5 into the fitting function to calculate the chloride ion content of the rust layer on the surface of the bronze artifact.
[0013] Specifically, in step 1), 0.03-0.05 g of chitosan and an equivalent amount of sodium alginate can be dissolved in 70-100 ml of deionized water, and then 20-35 ml of a 4-7% (mass percentage) polyvinyl alcohol aqueous solution is added at 25-35°C.
[0014] Furthermore, in step 1), 30-45 ml of 0.1 M silver nitrate solution may be added.
[0015] Specifically, in step 1), the drying temperature may be 40-60 °C, and the drying time may be 1-3 h.
[0016] Specifically, in step 3), the ALg-CS-Ag hydrogel can be cut into small pieces of 3 mm×10 mm×20 mm.
[0017] Furthermore, in step 5), the cross-sectional area of the fully swollen hydrogel is 4 mm×15 mm, and the effective length is 23 mm.
[0018] Specifically, in step 5), when performing the AC impedance test, the test instrument is chi310m, the AC amplitude is 30mV, and the frequency is set to 0.1-100000Hz.
[0019] Furthermore, in step 5), the fitting function is: y=1.15×10 -4 +4.977×10 -4 (x+Q), where y is the reciprocal of the resistance value, x is the chloride ion concentration, and Q is the environmental factor.
[0020] Further preferably, the environmental factor Q can be -0.04 to -0.06.
[0021] Compared with the prior art, the beneficial effects of the determination method of the present invention are as follows:
[0022] 1) The method of the present invention does not damage the surface of fragile bronze objects and does not leave any residue;
[0023] 2) The method of the present invention can adjust the value of the environmental factor Q according to different batches of bronze artifacts to achieve relative accuracy;
[0024] 3) The method of the present invention can simultaneously perform rust removal while measuring the chloride ion concentration on the surface of bronze artifacts. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 is a graph showing the AC impedance test results in Example 1;
[0026] Figure 2 Based on Figure 1 Obtained equivalent circuit diagram;
[0027] Figure 3 The relationship between the inverse resistance value of the hydrogel and the chloride ion concentration and the linear fitting curve are drawn;
[0028] Figure 4 This is the AC impedance test result diagram in Experimental Example 1;
[0029] Figure 5The rust removal effect of the hydrogel on an imitation bronze plate is shown before (a), during (b), and after (c) rust removal. (d) shows the rust removal effect of the hydrogel of the present invention on a large piece of authentic bronze artifact.
[0030] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) of the copper element in the hydrogel after adsorption of the imitation bronze plate in Experimental Example 2. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.
[0032] Example 1
[0033] A method for accurately measuring the chloride ion content on the surface of bronze ware, which specifically comprises the following steps:
[0034] 1) Hydrogel Synthesis: Dissolve chitosan (CS) (0.05 g) and sodium alginate (ALg) (0.05 g) in 80 ml of deionized water. Add 25 ml of a 4% polyvinyl alcohol solution at 25-35°C and stir continuously to prepare a homogenous sodium alginate-chitosan-polyvinyl alcohol solution. Filter the solution to remove undissolved chitosan. Add 35 ml of a 0.1 M silver nitrate (AgNO₃) solution, stir for 30 minutes, and pour into a Petri dish (10 cm radius). Dry the dish in a drying oven at 50°C for 1 hour to obtain the Alg-CS-Ag hydrogel.
[0035] 2) Preparation of artificial rust powder: Mix 2.00g of basic copper chloride with 0.00g, 0.002g, 0.01g, and 0.02g of copper chloride respectively, add them into 25ml beakers and shake the mixed powder until it is flat. The beakers are numbered A1, A2, A3, and A4, corresponding to Figure 1 The mass of free chloride ions in the solution accounts for 0.000%, 0.053%, 0.262% and 0.526% of the total mass.
[0036] 3) Adsorption Process: Cut the ALg-CS-Ag hydrogel obtained in step 1) into small pieces (3 mm × 10 mm × 20 mm) and add them to A1, A2, A3, and A4, ensuring that one side of the hydrogel is in full contact with the rust powder for adsorption. Simultaneously, apply a similarly sized piece of ALg-CS-Ag hydrogel to the surface rust layer of a bronze artifact fragment for adsorption, designated A5. Wait 24 hours, then remove or peel off the adsorbed hydrogel.
[0037] 4) Soak the adsorbed hydrogel obtained in step 3) in 10 ml of deionized water and wait for 12 hours until it is fully swollen. The hydrogels are numbered B1, B2, B3, B4, and B5 respectively. The cross-sectional area of the fully swollen hydrogel is 4 mm × 15 mm, and the effective length is 23 mm.
[0038] 5) Perform AC impedance testing on the fully swollen hydrogels obtained in step 4) using a Chi310m instrument, an AC amplitude of 30 mV, and a frequency setting of 0.1-100,000 Hz. Use software (included with the instrument, CSStudio6) to perform an equivalent circuit fit on the test results to determine the hydrogel's resistance. Plot the relationship between the reciprocal resistance values of hydrogels B1, B2, B3, and B4 and the chloride ion concentration, then perform a linear fit to obtain a fitting function. Substitute the reciprocal resistance value of hydrogel B5 into the fitting function to calculate the chloride ion content of the bronze surface rust layer.
[0039] The specific results are as follows:
[0040] Figure 1 The AC impedance test result diagram is given; Figure 2 Based on Figure 1 Obtained equivalent circuit diagram. Figure 1 、 Figure 2 The data information in the table was used to obtain the resistance values presented in Table 1. Table 1 shows the resistance values of the hydrogels obtained by the AC impedance test.
[0041] Table 1 Resistance values of hydrogels
[0042]
[0043] Figure 3 Based on the resistance values in Table 1 above, a relationship diagram of the corresponding hydrogel resistance reciprocal and chloride ion concentration and a linear fitting curve are drawn. Figure 3 It can be seen that the fitting function is: y=1.15×10 -4 +4.977×10 -4 x, where y is the reciprocal of the resistance value and x is the chloride ion concentration.
[0044] Determination of environmental factor Q:
[0045] Since artificial rust powder is different from actual rust layer in density, porosity and other factors, and the actual rust layer will change with the different environmental factors of the bronze artifact, these uncertain factors will affect the actual amount of chloride ions adsorbed by the hydrogel. Therefore, an environmental factor Q needs to be added to the fitting function, and the empirical formula is: y = 1.15 × 10 -4 +4.977×10 -4(x + Q), where the Q value is related to factors such as the density and porosity of the rust layer on the bronze surface. Here is a reference value of Q, Q = -0.0505, which is obtained as follows:
[0046] The rust layer on the surface of the bronze fragment in Example 1 was scraped off with a file, and the scraped mass was 0.2648 g. The obtained rust powder was immersed in 30 ml of deionized water and stirred for 1 hour. The chloride ion concentration was measured by using a PXSJ-216f ion meter. -3.809 mol / L, the chloride ion content of the rust layer on the bronze surface is converted to 0.0624%. Substituting the R resistance value 8273.1Ω corresponding to hydrogel B5 and the chloride ion content 0.0624% into the above empirical formula, the environmental factor Q = -0.0505 is obtained.
[0047] Test Example 1: The chloride ion concentration of two different fragments of the same batch of bronze artifacts in Example 1 was measured using the method of the present invention to verify the repeatability and stability of the determination method of the present invention.
[0048] The ALg-CS-Ag hydrogel blocks (3 mm × 10 mm × 20 mm) prepared in Example 1 were attached to the surface rust layer of two bronze fragments for adsorption and waited for 24 h. The adsorbed hydrogels were peeled off and immersed in 10 ml of deionized water for 12 h until they were completely swollen. The hydrogels were numbered B6 and B7 respectively. The fully swollen hydrogels were subjected to AC impedance testing (see the results). Figure 4 ), the test instrument is chi310m, the AC amplitude is 30mV, the frequency is set to 0.1-100000Hz, and the test results are fitted with an equivalent circuit, and the resistance values of the hydrogel are R(B6)=8937.8Ω and R(B7)=8854.6Ω. The reciprocal of the resistance value is calculated and substituted into the empirical formula y=1.15×10 -4 +4.977×10 -4 (x+Q), Q= -0.0505, and the chloride ion content of the rust layer on the surface of the bronze fragments was obtained to be 0.0442% (B6) and 0.0463% (B7), respectively.
[0049] Figure 4 The AC impedance test result diagram in Experiment 1 is given; Figure 4 The resistance values of the hydrogel can be obtained as R(B6)=8937.8Ω and R(B7)=8854.6Ω.
[0050] Use a file to scrape off the rust layer on the surface of the two bronze fragments mentioned above, and the scraped mass is 0.0367g and 0.0226 respectively. The obtained rust powder is immersed in 20ml of deionized water and stirred for 1h. The chloride ion concentration is measured by PXSJ-216f ion meter, which is 10 -4.656mol / L、0 -4.811 mol / L, the chloride ion content of the rust layer on the bronze fragments was calculated to be 0.0417% (B6) and 0.0485% (B7). Compared with existing measurement methods, the errors of the hydrogel measurement method of the present invention are 6% and -4.54%, respectively, both within the acceptable range of 10%.
[0051] The above experimental results demonstrate the repeatability and stability of the hydrogel determination method of the present invention for determining chloride ions.
[0052] Test Example 2: Testing the accuracy of the method of the present invention:
[0053] The Alg-CS-Ag hydrogel block (3 mm × 10 mm × 20 mm) prepared in Example 1 was attached to the surface rust layer of the imitation bronze plate for adsorption and waited for 24 h. The adsorbed hydrogel was peeled off and immersed in 10 ml of deionized water and waited for 12 h until it was completely swollen. The fully swollen hydrogel was subjected to an AC impedance test using a chi310m instrument with an AC amplitude of 30 mV and a frequency of 0.1-100000 Hz. The test results were fitted with an equivalent circuit to obtain a hydrogel resistance value R = 9909 Ω. The reciprocal of the resistance value was calculated and substituted into the empirical formula y = 1.15 × 10 -4 +4.977×10 -4 (x+Q), Q= -0.0505, and the chloride ion content of the rust layer on the surface of the imitation bronze plate is 0.02217%.
[0054] The rust layer on the surface of the imitation bronze plate was scraped off with a file, and the scraped mass was 0.0564 g. The obtained rust powder was immersed in 20 ml of deionized water and stirred for 1 hour. The chloride ion concentration was measured by using a PXSJ-216f ion meter. -2.915 mol / L, the chloride ion content of the rust layer on the imitation bronze plate is converted to 0.02296%, with an error of 3.56%. Since there is still a certain difference between the rust layer of the imitation bronze plate and the actual bronze artifact, this error is within the normal range.
[0055] Experimental Example 3: Determination of the Targeted Adsorption Capacity of the Hydrogel on Copper Rust by XPS Analysis
[0056] Figure 5 The rust removal effect of the hydrogel on the imitation bronze plate is shown in Figure 1, which is before (a), during (b) and after (c) rust removal. (d) shows the rust removal effect of the hydrogel of the present invention on a large real bronze artifact. Figure 5 It can be seen that: after rust removal using the method of the present invention and the hydrogel, the surface of the device is treated intact and undamaged, no residue remains on the device surface, and the rust removal effect is good.
[0057] In order to further understand the chemical state of copper in the hydrogel and the coordination between copper rust and the hydrogel network, the present invention conducted XPS analysis on the Alg-CS-Ag hydrogel after adsorbing the imitation bronze plate surface rust layer. The results are shown in Figure 2. Figure 6 . Figure 6 The X-ray photoelectron spectroscopy (XPS) of copper in the hydrogel after adsorption of a simulated bronze plate is presented. The figure shows that the binding energy of the surface charge was corrected to 284.5 eV using the C 1s peak of contaminated carbon as a reference. Comparison with the standard binding energy spectrum shows that the peak at 934.8 eV is attributed to Cu(II) in basic copper carbonate, accompanied by oscillatory satellite peaks (938-948 eV) characteristic of Cu(II). The strong peak at 936.5 eV is the result of a coordination reaction of Cu(II) in the basic copper carbonate, resulting in a change in binding energy. The atomic ratio of Cu(II) to uncoordinated Cu(II) is approximately 3:2. Therefore, the copper element exists primarily in the form of basic copper carbonate, most of which undergoes a strong coordination reaction with the PAAm-CS-Ag hydrogel. This coordination reaction results in the binding of carbonyl and amino groups in the hydrogel to copper ions. Macroscopically, the copper rust is fully adsorbed by the hydrogel, which accounts for the hydrogel's strong adsorption capacity for copper rust.
[0058] Figure 5 The rust removal effect of hydrogel on bronze artifacts was demonstrated on a macro scale. Figure 6 It shows the close bonding between copper rust and hydrogel at the microscopic level and explains the strong adsorption ability of hydrogel on copper rust from a mechanistic perspective.
[0059] The above test results show that the hydrogel in the present invention has a strong adsorption capacity for copper rust, thereby having a good rust removal effect, and can be used to accurately determine the chloride ion content of the rust layer on the surface of bronze ware.
Claims
1. A method for accurately measuring the chloride ion content of the rust layer on the surface of bronze ware, characterized in that: The steps include: 1) Hydrogel synthesis: Water-soluble chitosan and sodium alginate were dissolved in water, and then polyvinyl alcohol solution was added and stirred evenly. Then, silver nitrate solution was added and stirred, and dried to obtain ALg-CS-Ag hydrogel; 2) Preparation of artificial rust powder: Mix 2.00g of basic copper chloride with 0.00g, 0.002g, 0.01g, and 0.02g of copper chloride, respectively. Add to a beaker and shake until smooth. Number the mixture A1, A2, A3, and A4, respectively. 3) Adsorption process: Cut the ALg-CS-Ag hydrogel obtained in step 1) into small pieces and add them to A1, A2, A3, and A4, respectively, ensuring that one side of the hydrogel is in full contact with the rust powder for adsorption. Simultaneously, attach the ALg-CS-Ag hydrogel of the same size to the surface rust layer of the bronze fragment for adsorption, numbered A5. Wait 21-27 hours, then remove or peel off the adsorbed hydrogel. 4) Soaking the adsorbed hydrogel obtained in step 3) in deionized water until it is completely swollen. The hydrogels are numbered as B1, B2, B3, B4, and B5 respectively; 5) Performing an AC impedance test on the fully swollen hydrogel obtained in step 4), and performing an equivalent circuit fitting on the test results to obtain a resistance value; plotting the relationship between the reciprocal resistance values of hydrogels B1, B2, B3, and B4 and the chloride ion concentration and performing a linear fit to obtain a fitting function; substituting the reciprocal resistance value corresponding to hydrogel B5 into the fitting function to calculate the chloride ion content of the rust layer on the surface of the bronze artifact.
2. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 1, characterized in that: In step 1), 0.03-0.05 g of chitosan and an equivalent amount of sodium alginate are dissolved in 70-100 ml of water, and then 20-35 ml of 4-7% polyvinyl alcohol solution is added.
3. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 2, characterized in that: In step 1), add 30-45 ml of 0.1 M AgNO3 solution.
4. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 1, characterized in that: In step 1), the drying temperature is 40-60 °C and the drying time is 1-3 hours.
5. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 1, characterized in that: In step 3), the ALg-CS-Ag hydrogel was cut into small pieces of 3 mm × 10 mm × 20 mm.
6. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 5, characterized in that: In step 5), the cross-sectional area of the fully swollen hydrogel is 4 mm × 15 mm, and the effective length is 23 mm.
7. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 6, characterized in that: When performing the AC impedance test in step 5), the AC amplitude is 30mV and the frequency is set to 0.1-100000Hz.
8. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 7, characterized in that: In step 5), the fitting function is: y=1.15×10 -4 +4.977×10 -4 (x+Q), where y is the reciprocal of the resistance value, x is the chloride ion concentration, and Q is the environmental factor.
9. The method for accurately measuring the chloride ion content of the rust layer on the surface of bronze according to claim 8, characterized in that: The Q is -0.04 to -0.06.
